2021
DOI: 10.3390/ijerph18158228
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Explosive Force of the Elite Level Football-Tennis Players through Plyometric and Specific Exercises

Abstract: The aim of the research was to implement an athletic program to improve the explosive force in order to optimize physical fitness at the level of elite football-tennis players and evaluate the progress made through specific tests using the Opto Jump. The research included 10 elite European and world-class players, on whom an experimental program was applied in order to improve the explosive force of the limbs in conditions of speed, endurance, and dynamic balance. Study tests: five vertical jumps on the spot, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Thus, the authors concluded that HIIT is not superior to constant intensity endurance training (CIET) in improving aerobic or anaerobic parameters in adolescents. The research regarding the importance of SSG on the optimization of sports performance in sports games in general [54][55][56][57][58], and in football in particular, is numerous, as is made evident by their positive impact on psychological, physical, tactical and technical skills in the sports training process and in competitive games, for all age groups [59][60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the authors concluded that HIIT is not superior to constant intensity endurance training (CIET) in improving aerobic or anaerobic parameters in adolescents. The research regarding the importance of SSG on the optimization of sports performance in sports games in general [54][55][56][57][58], and in football in particular, is numerous, as is made evident by their positive impact on psychological, physical, tactical and technical skills in the sports training process and in competitive games, for all age groups [59][60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…In order to perform CMJ and SJ tests and obtain the jump height in centimetres, an Optojump TX10 (Bolzano, Italy) was used. This system, consisting of a transmitting and a receiving bar, allows measuring flight and contact times (Santos-Lozano et al, 2014), is portable, and adjustable to limited spaces (Gherghel et al, 2021).…”
Section: Vertical Jumpsmentioning
confidence: 99%
“…Plyometric exercises involve skips, hops, jumps, throws, and bounds. All these exercises improve the agility of an athlete, which is defined as the capability of a body to diligently change the position and direction of a body and move towards another position [6][7][8]. At first plyometric exercises were used for the enhancement of sports performance and rehabilitation of sports injuries numerous sports performance [9].…”
Section: Introductionmentioning
confidence: 99%